EVALUASI PROGRAM SERTIFIKASI HAK ATAS TANAH (SeHAT) NELAYAN DI KABUPATEN GUNUNGKIDUL TAHUN 2010 - , NOOR ICHSAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This article examines the policy of right certification of fishermenâs land in Gunungkidul Regency in 2010. Whether this policy has actually can change the fishermenâs land that had been passive capital into active capital so as to improve access of endeavor capital of fishermen and what the factors that affect any level of its success. It is the first policy conducted by the Gunungkidul Government in an effort to boost access of endeavor capital of fishermen to enhancement of business scale and other productive economic development. The goal ultimately is to improve the welfare of small fishermen. But in reality many experienced problems both in implementation and in the achievement of goals. The method used in this research is descriptive qualitative method. Data was collected by observation, interviews, and documentation as well as by combining all three techniques of data collection. While the location of the research conducted on three groups of fishermen in the three villages on the three different districts namely Kemadang Village in Tanjungsari District, Kanigoro Village in Saptosari District and Girikarto village in Panggang District. The results showed that, despite many obstacles, the pre and certification stage has been done well. Certification on 100 land parcels have transformed the land into active capital. However, there is one most important of certification stage has not implemented yet, the post-certification stage has not implemented yet because there is no follow-up and lack of budget. The utilization of land certificate to access of endeavor capital as different from one group to the other groups, but it can be said that most of the fishermen participants who had received land certificate have been utilize it to access of endeavor capital. The factors that influence the level of success of the policy of right certification of fishermenâs land in Gunungkidul Regency in 2010 are: 1) Resources include human resources of executor from the the district until to the village government, and budget execution which just until to the provincial level